PENERAPAN HUKUMAN DISIPLIN BAGI PEGAWAI NEGERI SIPIL YANG TIDAK MELAPORKAN STATUS PERCERAIANNYA - Evi Oktarina (Justici, 2023)
ABSTRACT Divorce can happen to anyone, including civil servants. According to Marsono, civil servants are civil servants who are full of loyalty to Pancasila, the 1945 Constitution and the government who are united, have good mentality, are highly disciplined, authoritative, efficient, have high quality and are aware of their responsibilities as the first element of the state apparatus. The method used in this paper is a normative method with a statutory approach, meaning that the approach is carried out by examining all relevant laws and regulations in accordance with the law being handled. The results obtained from this study are. To Civil Servants who do not report their divorce based on Article 15 paragraph (1) Government Regulation no. 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants which reads: Civil servants who do not report their divorce within a period of no later than one month from the date of the divorce, are subject to one of the severe disciplinary penalties